Shakespeare and amateur performance a cultural history - Dobson, Michael (Cambridge University Press, 2011)
"From the Hamlet acted on a galleon off Africa to the countless outdoor productions of A Midsummer Night's Dream that now defy each English summer, Shakespeare and Amateur Performance explores the unsung achievements of those outside the theatrical profession who have been determined to do Shakespeare themselves. Based on extensive research in previously unexplored archives, this generously illustrated and lively work of theatre history enriches our understanding of how and why Shakespeare's plays have mattered to generations of rude mechanicals and aristocratic dilettantes alike: from the days of the Theatres Royal to those of the Little Theatre Movement, from the pioneering Winter's Tale performed in eighteenth-century Salisbury to the Merchant of Venice performed by Allied prisoners for their Nazi captors, and from the how-to book which transforms Mercutio into Yankee Doodle to the Napoleonic counterspy who used Richard III as a tool of surveillance"-- Provided by publisher.